Integrating An-Nagaamat into Grammar Teaching: تطبيق النغمات في تعليم القواعد النحوية - Wildani, Wildani; Sani, Ahmad (Institut Agama Islam Negeri Lhokseumawe, 2025)
The science of nahwu is one of the fundamental branches of knowledge in Arabic, therefore, studying it is essential. Without Nahwu, one cannot fully understand Arabic. However, it is often perceived as difficult, particularly for beginners. Mastery of Nahwu is also crucial in reading classical texts known as Kitab Kuning. To address this issue, an appropriate method is needed to help students understand and memorize grammatical rules through the use of rythm. This study applies the rhythm methods as a learning strategy. The aim of this thesis is to determine the influence of the rhythm method on learning nahwu. The research employed a quantitative experimental approach, specifically a pre-experimental one group design. The population used was 15 students, all of whom were included. Data were collected using pre and post tests. The findings indicate that the rhythm method significantly improves learning nahwu outcomes, as evidenced by the Wilcoxon test result (p= 0.001 < 0.05), which supports the acceptance of the alternative hypothesis. Furthermore, the N-Gain Score test was 81. It can be concluded the use of the rhythm method has an influence on learning the rules of nahwu.